2008
DOI: 10.1016/j.aap.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate Poisson-lognormal regression model for prediction of crash counts by severity, using Bayesian methods

Abstract: The following paper is a pre-print and the final publication can be found in Accident Analysis and Prevention, 40 (3):964-975, 2008. Presented at the 86 th Annual Meeting of the Transportation Research Board, January 2007 ABSTRACT Numerous efforts have been devoted to investigating crash occurrence as related to roadway design features, environmental and traffic conditions. However, most of the research has relied on univariate count models; that is, traffic crash counts at different levels of severity are est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(146 citation statements)
references
References 48 publications
6
139
1
Order By: Relevance
“…Different approaches can be used for collision severity analysis: (a) incorporating severity into the collision frequency models by modeling collisions classified by severity types [31][32][33][34]; and (b) modeling the conditional probability of each severity level for a given collision [14,15,17,35,36]. In this research, we adopted the second approach for three reasons: (i) different factors could have different effects on collision occurrence and severity (e.g., seat belt use has nothing to do with collision occurrence, but is an important factor in severity analysis); (ii) data that could be used for joint models are limited in nature because most of the data are collected after the collision has happened [12]; and, (iii) consequence outcomes and injury data are at the individual, vehicle, or accident level.…”
Section: Model Developmentmentioning
confidence: 99%
“…Different approaches can be used for collision severity analysis: (a) incorporating severity into the collision frequency models by modeling collisions classified by severity types [31][32][33][34]; and (b) modeling the conditional probability of each severity level for a given collision [14,15,17,35,36]. In this research, we adopted the second approach for three reasons: (i) different factors could have different effects on collision occurrence and severity (e.g., seat belt use has nothing to do with collision occurrence, but is an important factor in severity analysis); (ii) data that could be used for joint models are limited in nature because most of the data are collected after the collision has happened [12]; and, (iii) consequence outcomes and injury data are at the individual, vehicle, or accident level.…”
Section: Model Developmentmentioning
confidence: 99%
“…Several multivariate models have been employed such as multivariate spatial models (Song, 2004;Song et al, 2006), multivariate Poisson (MVP) models (Ma and Kockelman, 2006), and multivariate Poisson-lognormal (MVPLN) models (Park and Lord, 2007;Ma et al, 2008;Aguero-Valverde and Jovanis, 2009;El-Basyouny and Sayed, 2009). Compared to the univariate modelling approach, the multivariate models (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…MVP or MVPLN) are argued to be superior since multivariate models can take account of correlation between different types of accidents, or in other words to "borrow strength" from similar sources (Song et al, 2006). However, as pointed out by Ma et al (2008), the superiority of the multivariate models compared to univariate models is not "theoretical" but rather "empirical". By comparing several Poisson based models using both the multivariate and univariate approach, Lan and Persaud (2010) found that univariate models fit the data better and outperform the multivariate models, and thus univariate models were recommended.…”
Section: Introductionmentioning
confidence: 99%
“…It is of key importance to relate crash occurrence with roadway design features too. In [19], a multivariate Poisson-lognormal specification is presented, that simultaneously models crash counts by injury severity. The results of such approach are useful for recommendations for highway safety treatments and design policies.…”
mentioning
confidence: 99%